Experimental and finite element evaluation of bending for mild steel - Ahmad Aiman, Ramlan (2012)
Finite element evaluation is one of the methods in predicting the springback angle in sheet metal bending. Predicting the springback is important since to produce the accuracy part geometry, the design of the die and bending tool must be accurate. This thesis aims to evaluate the reliability of finite element method by comparing the results with experimental results. The effect of parameters such as anisotropy in springback also has been studied. Abaqus software has been used to simulate the bending process and the mechanical properties provided from tensile test will be used to run the simulation. In the U-bending experiment, the die were clamped on stamping machine and the Mild Steel sheets then have been bent before the springback being measured with SolidWorks software. The results from the experiment and simulation is slightly different for the springback angle Ɵ1 , which the simulation shows increasing the orientation will increase the springback, and for the experimental, the springback higher at 0 degree orientation angle, and lower at 45 degree. For the springback angle Ɵ2 , the simulation and experimental result show that increasing the orientation angle will increase the amount of springback. Finite element method can be used to predict the springback since the pattern of the graphs are nearly the same and percentages of error are below 10 %. It can be comprehended that the finite element method are suitable method to predict the springback angle of sheet metal bending. The further study on parameters that effected bending process will make the finite element method is important in the future.